Tata Ruang di Perpustakaan Politeknik Negeri Padang - Wulandari, Elsy; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The purpose of this paper is to discussed about the spatial in the Library of Polytechnic State of Padang. The data collected through observation, interviews, and literature study with librarians in the Polytechnic State of Padang. Analyzing data is done descriptively. Based on analyzing the data, summarized the following matters. First, the Polytechnic State of Padang do not yet have their own building, but still use one of the existing political buildings. Second, the reading table does not have a diving wall, this couses distored reader concentration to read the collection in the library. Third, the Polytechnic State of Padang does not have the library materials processing room, due to limited building area then the library materials processing room does not exist, so the librarians rocess the library materials in the circulation room. This can interfere with the convenience and concentration of librarians in the library. Fourth, the limitations of the building area resulted in the conservation and preservation space not exist. Therefore, the librarian use the circulationÂ room and the staff work desk in the care of library materials.Keywords: library, spatial, Polytechnic State of Padang.